MEDIA MONTASE BERKARAKTER AGAMIS TERHADAP PEMBELAJARAN MENULIS TEKS NARASI BAGI SISWA TINGKAT - Dinda Diana Fitri; Rohmat Tri Sudrajat; Reka Yudha Mahardika (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
In research related to writing skills by developing media in the form of image media into montage media. Because in general, this montage media is included in the image media. It was found that there werw difficulties for students in writing narrative texts. Students find it difficult to make coherent sentences and experience impasse in making story ideas.Â  So the presence of this media, is very important to be studied so that it can be used. The method used in the research is R&D or Research and Development which is used to produse products and the feasibility of their development. The results obtained there areÂ  two trials at two schools said it was very strong with a percentage of 86%-90% on the object of limited trial. While in the wide trial, the percentage of the first class was 81%-88%, and the second class was 72%-78%. So, this media is assumed to be used in learning to write narrative texts, especially for student who need a visual depiction of what they are going to write. For schools that already have a more adequate technological infrastructure, it is advisable to try to apply this media with other media.